К изучению фауны жуков семейства Coccinellidae подзон типчаково-ковыльной и полынно-типчаково-ковыльной степи Левобережной Украины - Мизер, А.В. (Вестник зоологии, 1970)
In subzone of sheep’s fescue-feather-grass steppe 59 species (26 genera) of beetles from the Coccinellidae family were found. At the plateau 27 species are found, most of them are concentrated on the agricultural crops (23 species) and in forest belts (13 species). 13 species inhabit the slopes of ravines. The majority of Coccinellidae (32 species) inhabits the valleys of rivers, where 22 species (mainly, mesophilic forms) were found in broad-leaved forests and 25 species — in flow meadows. In the subzone of mugwort-sheep s fescue-feather-grass steppe 33 species (21 genera) of Coccinellidae are registered. The steppe xerophils are typical inhabitants of this subzone. II species are found on sandy-shelly bars, 8 — on solonchaks, 12 species (steppe xerophils predominating)—on the sea coast. As to the zoogeographical elements, the European ones are presented best of all.